2003
DOI: 10.1142/s0217979203021423
|View full text |Cite
|
Sign up to set email alerts
|

Josephson Effect in Pb/I/NbSe2 Scanning Tunneling Microscope Junctions

Abstract: We have developed a method for the reproducible fabrication of superconducting scanning tunneling microscope (STM) tips. We use these tips to form superconductor/insulator/superconductor tunnel junctions with the STM tip as one of the electrodes. We show that such junctions exhibit fluctuation dominated Josephson effects, and describe how the Josephson product IcRN can be inferred from the junctions' tunneling characteristics in this regime. This is first demonstrated for tunneling into Pb films, and then appl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…11 Josephson studies using a superconducting STM on conventional superconductors have shown good agreement between the measured I C R N and BCS predictions. 12,13 For high-T C superconductors, on the other hand, there is no established theory to relate I C R N with ⌬ derived from the quasiparticle excitation spectrum. There can be at least two additional issues not present for conventional superconductors.…”
Section: I C R N Productmentioning
confidence: 99%
“…11 Josephson studies using a superconducting STM on conventional superconductors have shown good agreement between the measured I C R N and BCS predictions. 12,13 For high-T C superconductors, on the other hand, there is no established theory to relate I C R N with ⌬ derived from the quasiparticle excitation spectrum. There can be at least two additional issues not present for conventional superconductors.…”
Section: I C R N Productmentioning
confidence: 99%
“…As a promising experimental tool to detect the spatial textures of competing superconducting order parameters and of MBS wave functions, we discuss JSTM [38][39][40][41][42][43] compute the expected signatures in the Jospheson current. We extend previous theoretical work (see, in particular, Ref.…”
Section: Detection By Jstmmentioning
confidence: 99%
“…Potential 28,29 . In addition, we show a JSTM [38][39][40][41][42][43] tip that allows to probe the spatial texture of the order parameter and of the MBS wave function as we discuss in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…The operation of this SC-STM has been demonstrated with the observation of Josephson tunneling between the tip and both SC Pb films [9] and SC NbSe 2 [10]. The signature Josephson response of the SC-STM differs from that of typical low R N planar S/I/S devices.…”
mentioning
confidence: 95%
“…Furthermore, this parameter is directly linked to both the SC order parameter amplitude and the energy gaps BCS of the materials through the BCS relationship. Josephson studies using a SC-STM on conventional superconductors were validated by the good agreement between the measured I C R N and BCS theory [9,10]. For HTSCs, on the other hand, there is no estab-lished theory to relate I C R N with derived from the QP excitation spectrum.…”
mentioning
confidence: 99%